Fiber-based porous affinity separation material with periodic necking pore structure and preparation method of fiber-based porous affinity separation material
By introducing periodic necked pore structures into porous affinity separation materials, using directional freeze-drying and grafting modification technologies, the problem of low contact efficiency of existing materials when liquids pass through is solved, and more efficient adsorption and separation effects are achieved .
Patent Information
- Application Number
- CN202411459203.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-19
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-18
AI Technical Summary
When the existing porous affinity separation materials pass through quickly, it is difficult to achieve high-efficiency contact and adsorption with the liquid, resulting in a contradictory problem between permeability and adsorption efficiency.
Directional freeze-drying method was used to mix two secondary pre-crosslinked modified nanofiber foam solutions with different viscosity to prepare nanofiber aerogels with periodic necked channel structure, and pass through spacer arm aqueous solution and aptamer aqueous solution. Two graft modifications were performed to form a fiber-based porous affinity separation material with a periodic necked pore structure.
By regulating the aerogel channel structure, the contact probability between the liquid and the channel wall is improved, the efficiency and speed of affinity modification are enhanced, the adsorption efficiency of the substance to be separated is improved, and a better separation effect is achieved.
Smart Images

Figure CN119488853A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filtering and separating materials, and in particular to a fiber-based porous affinity separation material with a periodic necking channel structure and a preparation method thereof. Background Art
[0002] Affinity separation materials are indispensable core materials in the biopharmaceutical industry. They are used to separate and purify drug solutions, extract key biological substances such as proteins and nucleic acids, and provide strong basic material support for the development of high value-added biological products and advanced biotherapy technologies. Common affinity separation materials are mainly porous materials such as polymer filler microsphere materials and aerogels. Both types of materials mainly rely on chemical functional groups with affinity adsorption properties fixed on the surface of their porous aerogels to adsorb and separate biological molecules. At the same time, these two types of materials have high porosity, which can ensure the smooth passage of drug solutions, showing great application value in the field of biological affinity separation.
[0003] The invention patent with publication number CN110498419A proposes a nano-silica particle for purification of histidine-tagged proteins and a preparation method thereof. The method comprises nano-SiO2 particles with a size of 50 to 100 nm. 2 The particle surface is amino-treated and then aldehyde-treated. After the metal chelate group is connected, the carbon-nitrogen double bond is reduced with sodium cyanoborohydride to enhance the metal chelate group and nano-SiO 2 Connection stability. Although the nano-silica particles prepared by the invention are small and have a high specific surface area, and as affinity separation materials for purifying histidine-tagged proteins, the protein separation and purification operation is simple and easy, but in actual application, chromatography columns need to be filled. The pores formed by the accumulation of small-sized particles are small, resulting in a slow flow rate of the drug solution and high resistance, which seriously affects the separation efficiency.
[0004] In view of the problem of slow separation speed of filler microsphere materials, the invention patent with publication number CN112194816A proposes a method for preparing modified cellulose aerogel for separating glycoproteins. The method uses cellulose aerogel as a substrate. Due to its advantages of three-dimensional network structure, low density, high specific surface area and large porosity, it can provide more binding sites for glycoproteins. Dendritic macromolecule polyethyleneimine (PEI) has rich functional groups and is easy to modify. By modifying it, the density of phenylboronic acid ligands can be increased, and the affinity for glycoproteins can be increased. The pore size of this material is large, which can ensure that the glycoprotein solution can pass quickly during the adsorption process, but it is difficult to ensure that the glycoprotein in the solution can be fully adsorbed, and it is still difficult to solve the contradiction between affinity adsorption capacity and separation speed.
[0005] The invention patent with the publication number CN114245757A proposes a structure-controllable ion exchange type nanofiber skeleton three-dimensional separation material and a preparation method thereof. The method prepares nanofibers by melt spinning, pre-disperses nanofibers, prepares a pre-crosslinked nanofiber suspension, and freeze-dries and cross-links to obtain a nanofiber skeleton three-dimensional separation material with a stable structure, a high specific surface area, and a large adsorption capacity. By regulating the composition and freezing method of the pre-crosslinked nanofiber suspension, the microstructure of the nanofiber skeleton three-dimensional separation material is regulated. When different amounts of polyelectrolytes are added to the pre-crosslinked nanofiber suspension, a high-strength and high-adsorption ion exchange type nanofiber skeleton three-dimensional separation material with diversified structures can be obtained, which can effectively improve the separation efficiency. However, the pores are all straight up and down structures, and the contact efficiency with the pore wall when the liquid passes through is still low. There is still a lot of room for structural optimization and separation performance improvement.
[0006] In view of this, it is necessary to design a fiber-based porous affinity separation material with a periodic necking pore structure and a preparation method thereof to solve the above problems. Summary of the invention
[0007] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a fiber-based porous affinity separation material with a periodic necking pore structure and a preparation method thereof. By constructing a fiber-based porous affinity separation material in which the pore walls are composed of periodically repeated necking structural units, the problem that the porous pores are difficult to achieve efficient contact and adsorption with the liquid when the liquid to be separated passes through quickly is solved, that is, the contradiction between permeability and adsorption efficiency is solved.
[0008] To achieve the above object, the present invention provides a fiber-based porous affinity separation material having a periodic necking channel structure and a preparation method thereof, comprising the following steps:
[0009] S1, mixing two secondary pre-crosslinked modified nanofiber foam solutions with different viscosities and then freeze-drying them to prepare a nanofiber aerogel with a periodic necking channel structure;
[0010] S2, using a spacer arm aqueous solution to perform a first grafting modification on the nanofiber aerogel prepared in step S1 to obtain a spacer arm modified nanofiber aerogel;
[0011] S3, using an aptamer aqueous solution to perform a second grafting modification on the spacer-arm modified nanofiber aerogel prepared in step S2, to obtain the fiber-based porous affinity separation material having a periodic necking channel structure.
[0012] Furthermore, in step S1, the two secondary pre-crosslinked modified nanofiber foam liquids with different viscosities include a secondary pre-crosslinked modified nanofiber foam liquid 1 with a viscosity of 1mPa·s≤X<10mPa·s and a secondary pre-crosslinked modified nanofiber foam liquid 2 with a viscosity of 10mPa·s≤X≤10000mPa·s.
[0013] Furthermore, in step S1, the preparation process of the secondary pre-crosslinked modified nanofiber foam liquid is as follows:
[0014] 1) Mixing and dispersing the copolymer nanofibers and the first crosslinking agent to obtain a pre-crosslinked modified nanofiber foam liquid;
[0015] 2) The pre-crosslinked modified nanofiber foam liquid is mixed and stirred with a second crosslinking agent, a chitosan aqueous solution, and a polyethyleneimine aqueous solution to obtain the secondary pre-crosslinked modified nanofiber foam liquid.
[0016] Furthermore, in step S1, the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.05-0.5wt.%, and the concentration of polyethyleneimine is 0.1-0.2wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5-5wt.%, and the concentration of polyethyleneimine is 0.2-1wt.%.
[0017] Furthermore, in step S2, the process of the first grafting modification is: placing the nanofiber aerogel in a closed container with an inlet and outlet, placing the spacer arm aqueous solution in an open container, entering the closed container through the inlet of the closed container by a peristaltic pump, then passing through the nanofiber aerogel, and then flowing out through the outlet of the closed container, and grafting the pore surface of the nanofiber aerogel for 0.5 to 2 hours at room temperature; in step S3, the process of the second grafting modification is: using the aptamer aqueous solution to perform the second grafting modification on the spacer arm modified nanofiber aerogel according to the steps of the first grafting modification in step S2.
[0018] Furthermore, in step S2 and step S3, the concentration range of the spacer arm aqueous solution and the aptamer aqueous solution is 1 to 10 wt.%; the spacer arm molecule in the spacer arm aqueous solution includes one of glutaraldehyde, adipaldehyde, pentamethylenediamine, and hexamethylenediamine; the ligand molecule in the aptamer aqueous solution includes one of the aptamers of CD63, CD9, CD81 with an amino or aldehyde terminal group, protein A, and protein G.
[0019] The present invention also provides a fiber-based porous affinity separation material with a periodic necking pore structure prepared by the preparation method, wherein the pore wall of the fiber-based porous affinity separation material is composed of periodically repeated necking structural units; the necking structural units include a fiber network skeleton and a polymer functional layer with affinity adsorption function attached to the surface of the fiber network skeleton.
[0020] Furthermore, the fiber network skeleton is composed of copolymer nanofibers; the copolymer nanofibers include ethylene vinyl alcohol copolymer nanofibers.
[0021] Furthermore, the polymer functional layer is cross-linked by a polymer cross-linked network layer, a spacer arm and an affinity ligand; the polymer cross-linked network layer is cross-linked by chitosan, polyethyleneimine and glutaraldehyde; and the affinity ligand is an aptamer with an amino or aldehyde terminal group.
[0022] Furthermore, the necking structure unit is a structure with small apertures at both ends and a large aperture in the middle, or with a large aperture at both ends and a small aperture in the middle.
[0023] The beneficial effects of the present invention are:
[0024] 1. A fiber-based porous affinity separation material with a periodic necking channel structure and a preparation method thereof provided by the present invention is prepared by mixing two specially prepared secondary pre-crosslinked modified nanofiber foam liquids with different viscosities and then freeze-drying them to prepare a nanofiber aerogel with a periodic necking channel structure, and then grafting and modifying the nanofiber aerogel twice with a spacer arm aqueous solution and an aptamer aqueous solution in sequence to obtain a fiber-based porous affinity separation material with a periodic necking channel structure. This method can complete the regulation of the aerogel channel by only preparing foam liquids with different viscosities, and the process is simple and efficient.
[0025] 2. The fiber-based porous affinity separation material with a periodic necking channel structure provided by the present invention selects green organic molecules containing amino groups and aldehyde groups, and adopts flow chemistry methods to carry out multiple chemical reactions during multiple cross-linking, spacer arm grafting modification, and ligand grafting modification to complete the preparation of the porous separation material. The whole process has the advantages of being green and pollution-free.
[0026] 3. The fiber-based porous affinity separation material with a periodic necking channel structure provided by the present invention regulates the contact probability between the liquid and the channel wall by means of the change in the size of the pore size in the flow direction of the liquid. On the one hand, it can improve the efficiency and speed of affinity modification, and on the other hand, it can improve the adsorption efficiency of the substance to be separated in the liquid, thereby having a more excellent implementation effect in both the preparation process and the separation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of the structure of a fiber-based porous affinity separation material having a periodic necked pore structure provided by the present invention;
[0028] Figure 2 Schematic diagram of stress variation of materials prepared when the chitosan concentration in the nanofiber foam solution 1 used in Example 1 is 0.05wt.% and the chitosan concentration in the nanofiber foam solution 1 used in Example 2 is 0.5wt.% under compressive strain;
[0029] Figure 3 This is a microstructure diagram of the fiber-based porous affinity separation material with a periodic necked channel structure prepared in Example 1;
[0030] Figure 4 Schematic diagram of strength change when the concentration of polyethyleneimine in the nanofiber foam solution 1 used in Example 3 is 0.15wt.% and the concentration of polyethyleneimine in the nanofiber foam solution 1 used in Comparative Example 4 is 1wt.%;
[0031] Figure 5 The electron microscope images of the structures corresponding to the materials prepared in Example 1 and Example 4 (upper row from left to right) and Comparative Example 5 and Comparative Example 6 (lower row from left to right) respectively;
[0032] Figure 6 This is an electron microscope image of the material structure prepared in Example 5. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0035] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0036] A method for preparing a fiber-based porous affinity separation material having a periodic necked channel structure comprises the following steps:
[0037] S1. Mixing two nanofiber foam solutions modified by secondary pre-crosslinking with different viscosities and then directional freeze-drying them to prepare a nanofiber aerogel with a periodic necking channel structure; the two nanofiber foam solutions modified by secondary pre-crosslinking with different viscosities include a nanofiber foam solution 1 modified by secondary pre-crosslinking with a viscosity of 1 mPa·s≤X<10 mPa·s and a nanofiber foam solution 2 modified by secondary pre-crosslinking with a viscosity of 10 mPa·s≤X≤10000 mPa·s;
[0038] The preparation process of the secondary pre-crosslinked modified nanofiber foam liquid is as follows:
[0039] 1) melt-extruding the sea phase polymer to prepare copolymer nanofibers;
[0040] The marine polymer comprises a mixture of copolymer masterbatch and cellulose acetate butyrate; the copolymer masterbatch comprises polyethylene-vinyl alcohol copolymer particles; the mass ratio of the polyethylene-vinyl alcohol copolymer particles to the cellulose acetate butyrate is 2:8 to 3:7; the average diameter of the copolymer nanofibers ranges from 50 to 1000 nm;
[0041] 2) mixing the copolymer nanofibers with a first crosslinking agent aqueous solution having a concentration of 1 to 5 wt.% at a mass ratio of 1:20 to 1:30, and dispersing the mixture for 10 to 20 minutes using an emulsifier, and obtaining a pre-crosslinked modified nanofiber foam liquid after the reaction is completed;
[0042] 3) Mixing the pre-crosslinked modified nanofiber foam liquid with a second crosslinking agent aqueous solution with a concentration of 1 to 5 wt.%, a chitosan aqueous solution with a concentration of 0.05 to 5%, and a polyethyleneimine aqueous solution with a concentration of 0.1 to 1% at a volume ratio of 1:0.3:2:0.5 to 1:0.1:1:0.1, and stirring at a constant speed for 18 to 25 minutes to obtain a secondary pre-crosslinked modified nanofiber foam liquid;
[0043] The first cross-linking agent aqueous solution and the second cross-linking agent aqueous solution both include glutaraldehyde solution;
[0044] The directional freeze-drying process is as follows: placing the mixed two secondary pre-crosslinked modified nanofiber foam liquids of different average diameters on a metal block, immersing the metal block in a solution at a temperature of -209°C to -40°C; the solution includes one of ethanol, isopropanol, and liquid nitrogen; and performing the directional freeze-drying for 46 to 50 hours;
[0045] S2, using a spacer arm aqueous solution to perform a first grafting modification on the nanofiber aerogel prepared in step S1 to obtain a spacer arm modified nanofiber aerogel;
[0046] S3, using an aptamer aqueous solution to perform a second grafting modification on the spacer-arm modified nanofiber aerogel prepared in step S2, to obtain the fiber-based porous affinity separation material having a periodic necking channel structure.
[0047] In step S2, the process of the first grafting modification is: placing the nanofiber aerogel in a closed container with an inlet and an outlet, placing the spacer arm aqueous solution in an open container, entering the closed container through the inlet of the closed container by a peristaltic pump, then passing through the nanofiber aerogel, and then flowing out through the outlet of the closed container, and grafting the pore surface of the nanofiber aerogel at room temperature for 0.5 to 2 hours;
[0048] In step S3, the process of the second grafting modification is: using the aptamer aqueous solution to perform the second grafting modification on the spacer arm modified nanofiber aerogel according to the steps of the first grafting modification in step S2.
[0049] In step S2 and step S3, the concentration range of the spacer arm aqueous solution and the aptamer aqueous solution is 1 to 10 wt.%; the spacer arm molecule in the spacer arm aqueous solution includes one of glutaraldehyde, adipaldehyde, pentamethylenediamine, and hexamethylenediamine; the ligand molecule in the aptamer aqueous solution includes one of the aptamers of CD63, CD9, CD81 with an amino or aldehyde terminal group, protein A, and protein G.
[0050] In this way, by mixing two nanofiber foam solutions with different viscosities and performing directional freeze drying, and then performing two grafting modifications, a fiber-based porous affinity separation material with a periodic necking channel structure capable of regulating the aerogel pores can be obtained. Among them, green organic molecules containing amino groups and aldehyde groups are selected, and a flow chemistry method is used to perform multiple chemical reactions in the process of multiple crosslinking, spacer arm grafting modification, and ligand grafting modification to complete the preparation of the porous separation material. This process is not only simple and efficient, but also has the advantages of being green and pollution-free.
[0051] Specifically, in some embodiments of the present invention, the chitosan concentration in the secondary pre-crosslinked modified nanofiber foam liquid one is 0.05-0.5wt.%, and the concentration of polyethyleneimine is 0.1-0.2wt.%; the chitosan concentration in the secondary pre-crosslinked modified nanofiber foam liquid two is 0.5-5wt.%, and the concentration of polyethyleneimine is 0.2-1wt.%.
[0052] With such arrangement, the aerogel prepared from the nanofiber foam liquid modified by secondary pre-crosslinking prepared with low concentration of chitosan has a fiber spherical structure, and the aerogel prepared from the nanofiber foam liquid modified by secondary pre-crosslinking prepared with high concentration of chitosan has a sheet-like or honeycomb structure, thus paving the way for the subsequent preparation of a fiber-based porous affinity separation material with a periodic necking channel structure, in which the thin part is sheet-like or honeycomb-like, and the thick part is a fiber spherical structure.
[0053] The present invention also provides a fiber-based porous affinity separation material with a periodic necking channel structure prepared by the preparation method, wherein the channel wall of the fiber-based porous affinity separation material is composed of periodically repeated necking structural units; the necking structural unit comprises a fiber network skeleton, and a polymer functional layer with affinity adsorption function attached to the surface of the fiber network skeleton;
[0054] The fiber network skeleton is composed of copolymer nanofibers; the copolymer nanofibers include ethylene vinyl alcohol copolymer nanofibers;
[0055] The polymer functional layer is formed by cross-linking a polymer cross-linked network layer, a spacer arm and an affinity ligand; the polymer cross-linked network layer is formed by cross-linking chitosan, polyethyleneimine and glutaraldehyde; the affinity ligand is an aptamer with an amine or aldehyde terminal group;
[0056] The aperture size of the necking structure unit in a direction perpendicular to the axial direction of the channel varies with the axial position, and forms a structure with small apertures at both ends and large apertures in the middle or large apertures at both ends and small apertures in the middle.
[0057] In this way, the prepared fiber-based porous affinity separation material with a periodic necking pore structure with small pore diameters at both ends and a large pore diameter in the middle or large pore diameters at both ends and a small pore diameter in the middle can regulate the contact probability between the liquid and the pore wall by virtue of the change in the size of the pore diameter in the flow direction of the liquid. On the one hand, it can improve the efficiency and speed of affinity modification, and on the other hand, it can improve the adsorption efficiency of the substance to be separated in the liquid, thereby having a more excellent implementation effect in both the preparation process and the separation process.
[0058] The fiber-based porous affinity separation material with a periodic necking channel structure and the preparation method thereof provided by the present invention are specifically described below in conjunction with the embodiments:
[0059] Example 1
[0060] This embodiment provides a method for preparing a fiber-based porous affinity separation material having a periodic necked channel structure, which specifically comprises the following steps:
[0061] S1, mixing a second pre-crosslinked modified nanofiber foam liquid 1 with a viscosity of 1 mPa·s and a second pre-crosslinked modified nanofiber foam liquid 2 with a viscosity of 10 mPa·s, and then directional freeze-drying for 48 hours to prepare a nanofiber aerogel with a periodic necking channel structure;
[0062] The directional freeze-drying process is as follows: placing the mixed two secondary pre-crosslinked modified nanofiber foam liquids on a copper block, and immersing the copper block in liquid nitrogen at a temperature of -100°C;
[0063] The preparation process of the secondary pre-crosslinked modified nanofiber foam liquid is as follows:
[0064] 1) melt-extruding the sea phase polymer to prepare copolymer nanofibers;
[0065] The marine polymer comprises a mixture of copolymer masterbatch and cellulose acetate butyrate; the copolymer masterbatch comprises polyethylene-vinyl alcohol copolymer particles; the mass ratio of the polyethylene-vinyl alcohol copolymer particles to the cellulose acetate butyrate is 2:8;
[0066] 2) respectively mixing the two copolymer nanofibers having different average diameters with a glutaraldehyde solution having a concentration of 1 wt.% at a mass ratio of 1:20 and dispersing them in an emulsifier for 15 minutes, and obtaining a pre-crosslinked modified nanofiber foam liquid after the reaction is completed;
[0067] 3) Mixing the pre-crosslinked modified nanofiber foam liquid with a glutaraldehyde solution with a concentration of 1wt.%, a chitosan aqueous solution with a concentration of 0.05wt.%, and a polyethyleneimine aqueous solution with a concentration of 0.1wt.% at a volume ratio of 1:0.3:2:0.5, and stirring at a constant speed for 20 minutes to obtain a secondary pre-crosslinked modified nanofiber foam liquid 1 with a viscosity of 1mPa·s;
[0068] The pre-crosslinked modified nanofiber foam liquid was mixed with a glutaraldehyde solution with a concentration of 1 wt.%, a chitosan aqueous solution with a concentration of 0.5 wt.%, and a polyethyleneimine aqueous solution with a concentration of 0.2 wt.% at a volume ratio of 1:0.3:2:0.5, and stirred at a constant speed for 20 minutes to obtain a secondary pre-crosslinked modified nanofiber foam liquid II with a viscosity of 10 mPa·s;
[0069] S2, the process of the first grafting modification is: placing the nanofiber aerogel prepared in step S1 in a closed container with an inlet and an outlet, placing a glutaraldehyde aqueous solution with a concentration of 1wt.% in an open container, entering the closed container through the inlet of the closed container by a peristaltic pump, then passing through the nanofiber aerogel, and then flowing out through the outlet of the closed container, at room temperature, grafting the pore surface of the nanofiber aerogel for 1h to obtain a spacer arm modified nanofiber aerogel;
[0070] S3. Place the nanofiber aerogel treated in step S2 in a closed container with an inlet and outlet, place an aptamer aqueous solution with a ligand molecule of protein A at a concentration of 1wt.% in an open container, enter the closed container through the inlet of the closed container through a peristaltic pump, then pass through the nanofiber aerogel treated in step S2, and then flow out through the outlet of the closed container. At room temperature, graft modification is performed on the pore surface of the nanofiber aerogel treated in step S2 for 1h to obtain the fiber-based porous affinity separation material with a periodic necking pore structure.
[0071] The fiber-based porous affinity separation material with a periodic necking pore structure prepared by the above-mentioned preparation method in this embodiment is applied to the separation and purification of biomacromolecules. The unique pore structure design of the material not only increases the specific surface area and provides more binding sites, but also effectively regulates the molecular diffusion and screening process through the periodic necking structure, thereby achieving efficient capture and release of target biomacromolecules.
[0072] Embodiments 2 to 7
[0073] Examples 2 to 7 respectively provide a fiber-based porous affinity separation material having a periodic necking channel structure and a preparation method thereof, which differs from Example 1 in that the concentrations of chitosan and polyethyleneimine in the two secondary pre-crosslinked modified nanofiber foam solutions used in step S1 are different:
[0074] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution 1 in Example 2 is 0.5wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0075] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution in Example 3 is 0.05wt.%, and the concentration of polyethyleneimine is 0.15wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0076] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution 1 in Example 4 is 0.05wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 5wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0077] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution in Example 5 is 0.05wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5wt.%, and the concentration of polyethyleneimine is 1wt.%.
[0078] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution in Example 6 is 0.4wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 5wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0079] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution 1 in Example 7 is 0.4wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 5wt.%, and the concentration of polyethyleneimine is 1wt.%.
[0080] The remaining steps are consistent with those in Example 1 and will not be repeated here.
[0081] Comparative Examples 1 to 8
[0082] Comparative Examples 1 to 8 respectively provide a fiber-based porous affinity separation material having a periodic necking channel structure and a preparation method thereof, which differs from Example 1 in that the concentrations of chitosan and polyethyleneimine in the two secondary pre-crosslinked modified nanofiber foam solutions used in step S1 are different:
[0083] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution 1 in Comparative Example 1 is 0.01wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0084] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution 1 in Comparative Example 2 is 0.8wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0085] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution 1 in Comparative Example 3 is 0.05wt.%, and the concentration of polyethyleneimine is 0.01wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0086] In Comparative Example 4, the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution 1 is 0.05wt.%, and the concentration of polyethyleneimine is 1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution 2 is 0.5wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0087] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution in Comparative Example 5 is 0.05wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.1wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0088] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution in Comparative Example 6 is 0.05wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 7wt.%, and the concentration of polyethyleneimine is 0.2wt.%.
[0089] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution in Comparative Example 7 is 0.05wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5wt.%, and the concentration of polyethyleneimine is 0.1wt.%.
[0090] The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution in Comparative Example 8 is 0.05wt.%, and the concentration of polyethyleneimine is 0.1wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5wt.%, and the concentration of polyethyleneimine is 3wt.%.
[0091] The remaining steps are consistent with those in Example 1 and will not be repeated here.
[0092] The changes of parameters in each step of the embodiment and the comparative example are shown in Table 1. By comparing the experimental results of Examples 1-2 and Comparative Examples 1-2, it is found that when the chitosan concentration in the prepared secondary pre-crosslinked modified nanofiber foam solution 1 gradually increases within the range of 0.05-0.5wt.%, the strength of the obtained fiber-based porous affinity separation material with a periodic necking channel structure is significantly improved (e.g. Figure 2As shown in Figure 2, the compression rebound performance gradually increases with the increase of chitosan concentration, which is also beneficial to Figure 3 The formation of the spherical structure shown. However, when the chitosan concentration is lower than this range, the obtained fiber-based porous affinity separation material with a periodic necking channel structure is almost inelastic. This is because when the chitosan concentration is too low, it is impossible to form a bridge between the nanofibers, and the connection is only based on the action between the nanofibers. When subjected to external forces, the nanofibers cannot support each other, resulting in the strength of the nanofiber material being too weak, making it unsuitable for experiments, and also unable to form a spherical structure. When the chitosan concentration exceeds this range, the surface morphology of the obtained fiber-based porous affinity separation material with a periodic necking channel structure will change. This is because when the chitosan solution concentration is high, the polyethyleneimine solution will undergo a cross-linking reaction with glutaraldehyde and chitosan, which will cause the morphology of the nanofiber material to change from a spherical structure to a lamellar structure, which is not conducive to the formation of a material with a periodic necking channel structure.
[0093] By comparing the experimental results of Example 1, Example 3 and Comparative Examples 3 to 4, it is found that when the concentration of polyethyleneimine in the prepared secondary pre-crosslinked modified nanofiber foam solution 1 gradually increases within the range of 0.1 to 0.2 wt.%, the obtained fiber-based porous affinity separation material with a periodic necking channel structure has more binding sites, that is, the polyethyleneimine solution contains amine groups. The higher the concentration, the more amine groups there are, which is more conducive to subsequent grafting modification. However, when the polyethyleneimine concentration is lower than this range, the obtained fiber-based porous affinity separation material with a periodic necking channel structure has only weak amine groups on the surface, which will result in a low grafting content and is not conducive to the subsequent filtration and separation of biomacromolecules. When the polyethyleneimine concentration exceeds this range, the strength of the obtained fiber-based porous affinity separation material with a periodic necking channel structure becomes weaker (such as Figure 4 This is because the glutaraldehyde solution, chitosan solution and polyethyleneimine solution will undergo a cross-linking reaction. When the polyethyleneimine solution is too high, the polyethyleneimine will instantly cross-link with the chitosan solution, while ignoring the existence of nanofibers, which is not conducive to the formation of a spherical structure.
[0094] By comparing the experimental results of Example 1, Example 4 and Comparative Examples 5 to 6, it is found that when the chitosan concentration in the prepared secondary pre-crosslinked modified nanofiber foam solution 2 gradually increases within the range of 0.5 to 5 wt.%, the strength of the obtained fiber-based porous affinity separation material with a periodic necking channel structure gradually increases, and the honeycomb structure becomes more and more obvious (such as Figure 5As shown), it is beneficial to the formation of the subsequent periodic necking channel structure. However, when the chitosan concentration is lower than this range, the obtained fiber-based porous affinity separation material with a periodic necking channel structure cannot form a sheet-like and honeycomb structure. When the chitosan concentration exceeds this range, the presence of nanofibers in the obtained fiber-based porous affinity separation material with a periodic necking channel structure will be ignored. This is because when the concentration of the chitosan solution is too high, the nanofibers will be enclosed in the chitosan solution, resulting in the presence of few nanofibers on the surface of the obtained fiber-based porous affinity separation material with a periodic necking channel structure, which will affect the subsequent grafting and filtration separation of biomacromolecules.
[0095] By comparing the experimental results of Example 1, Example 5 and Comparative Examples 7 to 8, it is found that when the concentration of polyethyleneimine in the prepared secondary pre-crosslinked modified nanofiber foam solution 2 gradually increases within the range of 0.2 to 1 wt.%, the honeycomb structure of the obtained fiber-based porous affinity separation material with a periodic necking channel structure is more regular (such as Figure 6 As shown), the grafting rate and adsorption capacity are getting higher and higher. However, when the concentration of polyethyleneimine is lower than this range, the obtained fiber-based porous affinity separation material with a periodic necking channel structure has fewer functional groups on the surface, which will lead to a relatively low grafting rate in the subsequent grafting process, affecting the final biomacromolecule filtration separation effect. When the concentration of polyethyleneimine exceeds this range, the strength of the obtained fiber-based porous affinity separation material with a periodic necking channel structure will weaken, and the underwater memory resilience will also weaken. This is because when the concentration of polyethyleneimine is too high, it will instantly cross-link with the chitosan solution and glutaraldehyde when added to the solution and instantly solidify, while ignoring the role of nanofibers, which will affect the compression resilience of the material.
[0096] By comparing Example 5 and Comparative Example 8, it can be seen that increasing the concentration of polyethyleneimine does not change the grafting rate much, and the rebound effect is not as good as that of Example 5. At the same time, the cost of the reagents used in Comparative Example 8 is also higher.
[0097] This shows that the effects of the prepared fiber-based porous affinity separation material with a periodic necking channel structure are all the result of the effects of various parameters.
[0098] Table 1 Experimental parameter settings for embodiments and comparative examples
[0099]
[0100]
[0101] In summary, the present invention provides a method for preparing a fiber-based porous affinity separation material with a periodic necking channel structure. By mixing two nanofiber foam liquids with different viscosities and performing directional freeze-drying, and then performing two grafting modifications, a fiber-based porous affinity separation material with a periodic necking channel structure that can regulate the aerogel channel can be obtained. Among them, green organic molecules containing amino groups and aldehyde groups are selected, and a flow chemistry method is used to perform multiple chemical reactions during multiple crosslinking, spacer arm grafting modification, and ligand grafting modification to complete the preparation of the porous separation material. This process is not only simple and efficient but also has the advantages of being green and pollution-free. In addition, the aerogel prepared by the nanofiber foam liquid prepared by the secondary pre-crosslinking modification of low-concentration chitosan has a fiber ball structure, and the aerogel prepared by the nanofiber foam liquid prepared by the secondary pre-crosslinking modification of high-concentration chitosan has a sheet-like or honeycomb structure, which also paves the way for the subsequent preparation of a fiber-based porous affinity separation material with a periodic necking channel structure. The present invention also provides a fiber-based porous affinity separation material with a periodic necking channel structure, wherein the channel wall is composed of periodically repeated necking structural units. Because it has a structure with small pore diameters at both ends and a large pore diameter in the middle or large pore diameters at both ends and a small pore diameter in the middle, it can regulate the contact probability between the liquid and the channel wall by means of the change in the size of the pore diameter in the flow direction of the liquid. On the one hand, it can improve the efficiency and speed of affinity modification, and on the other hand, it can improve the adsorption efficiency of the substance to be separated in the liquid, thereby having a more excellent implementation effect in both the preparation process and the separation process.
[0102] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a fiber-based porous affinity separation material having a periodic necking channel structure, characterized in that: The steps include: S1, mixing two secondary pre-crosslinked modified nanofiber foam solutions with different viscosities and then freeze-drying them to prepare a nanofiber aerogel with a periodic necking channel structure; S2, using a spacer arm aqueous solution to perform a first grafting modification on the nanofiber aerogel prepared in step S1 to obtain a spacer arm modified nanofiber aerogel; S3, using an aptamer aqueous solution to perform a second grafting modification on the spacer-arm modified nanofiber aerogel prepared in step S2, to obtain the fiber-based porous affinity separation material having a periodic necking channel structure.
2. The fiber-based porous affinity separation material with a periodic necked channel structure according to claim 1, characterized in that: In step S1, the two secondary pre-crosslinked modified nanofiber foam liquids with different viscosities include a secondary pre-crosslinked modified nanofiber foam liquid 1 with a viscosity of 1mPa·s≤X<10mPa·s and a secondary pre-crosslinked modified nanofiber foam liquid 2 with a viscosity of 10mPa·s≤X≤10000mPa·s.
3. The fiber-based porous affinity separation material with a periodic necked channel structure according to claim 2, characterized in that: In step S1, the preparation process of the secondary pre-crosslinked modified nanofiber foam liquid is as follows: 1) Mixing and dispersing the copolymer nanofibers and the first crosslinking agent to obtain a pre-crosslinked modified nanofiber foam liquid; 2) The pre-crosslinked modified nanofiber foam liquid is mixed and stirred with a second crosslinking agent, a chitosan aqueous solution, and a polyethyleneimine aqueous solution to obtain the secondary pre-crosslinked modified nanofiber foam liquid.
4. The method for preparing a fiber-based porous affinity separation material having a periodic necked channel structure according to claim 3, characterized in that: The chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.05-0.5wt.%, and the concentration of polyethyleneimine is 0.1-0.2wt.%; the chitosan concentration in the second pre-crosslinked modified nanofiber foam solution is 0.5-5wt.%, and the concentration of polyethyleneimine is 0.2-1wt.%.
5. The method for preparing a fiber-based porous affinity separation material having a periodic necked channel structure according to claim 1, characterized in that: In step S2, the process of the first grafting modification is: placing the nanofiber aerogel in a closed container with an inlet and outlet, placing the spacer arm aqueous solution in an open container, entering the closed container through the inlet of the closed container by a peristaltic pump, then passing through the nanofiber aerogel, and then flowing out through the outlet of the closed container, at room temperature, the pore surface of the nanofiber aerogel is grafted for 0.5 to 2 hours; in step S3, the process of the second grafting modification is: using the aptamer aqueous solution to perform the second grafting modification on the spacer arm modified nanofiber aerogel according to the steps of the first grafting modification in step S2.
6. The method for preparing a fiber-based porous affinity separation material having a periodic necked channel structure according to claim 5, characterized in that: In step S2 and step S3, the concentration range of the spacer arm aqueous solution and the aptamer aqueous solution is 1 to 10 wt.%; the spacer arm molecule in the spacer arm aqueous solution includes one of glutaraldehyde, adipaldehyde, pentamethylenediamine, and hexamethylenediamine; the ligand molecule in the aptamer aqueous solution includes one of the aptamers of CD63, CD9, CD81 with an amino or aldehyde terminal group, protein A, and protein G.
7. A fiber-based porous affinity separation material having a periodic necking channel structure, characterized in that: The pore walls of the fiber-based porous affinity separation material are composed of periodically repeated necking structural units; the necking structural units include a fiber network skeleton and a polymer functional layer with affinity adsorption function attached to the surface of the fiber network skeleton.
8. The fiber-based porous affinity separation material with a periodic necked channel structure according to claim 7, characterized in that: The fiber network skeleton is composed of copolymer nanofibers; the copolymer nanofibers include ethylene vinyl alcohol copolymer nanofibers.
9. The fiber-based porous affinity separation material with a periodic necked channel structure according to claim 8, characterized in that: The polymer functional layer is formed by cross-linking a polymer cross-linked network layer, a spacer arm and an affinity ligand; the polymer cross-linked network layer is formed by cross-linking chitosan, polyethyleneimine and glutaraldehyde; and the affinity ligand is an aptamer with an amino group or an aldehyde group as the terminal group.
10. The fiber-based porous affinity separation material with a periodic necked channel structure according to claim 8, characterized in that: The necking structure unit is a structure with small apertures at both ends and a large aperture in the middle, or with a large aperture at both ends and a small aperture in the middle.
Citation Information
Patent Citations
Nano-silica particles for purifying histidine tag protein and preparation method for nano-silica particles
CN110498419A
Preparation method of modified cellulose aerogel for separating glycoprotein
CN112194816A
Ion exchange type nanofiber skeleton three-dimensional separation material with controllable structure and preparation method of ion exchange type nanofiber skeleton three-dimensional separation material
CN114245757A
Nanofiber aerogel material for strong anion exchange and preparation method thereof
CN115286886A
Graphene-based thin film with macropore-micropore alternating structure
CN116789460A